Current Approaches in Cardiac Repair: Somatic and Stem Cell Exosomes - Yuka, Selcen Ari; Aslan, Ayca (SPRINGERNATURE, 2023)
Purpose of ReviewMyocardial infarction, which is the most important clinical sign of coronary artery disease, is one of the leading causes of global mortality, despite current treatment methods. Stem cell transplantation, which fastens on the regeneration of damaged tissue, has been suggested as an alternative approach in cardiac regenerative medicine; however, complications such as low survival in ischemic conditions, immune rejection, and teratoma formation have limited the routine use of stem cells in clinical treatments.Recent FindingsExosomes, which have been shown to play an essential role in intracellular communication and carry protein, lipid, and nucleic acid-based rich cargo content, have emerged as a new potential in the diagnosis and treatment of many diseases such as neurodegenerative diseases, cancer, and cardiovascular diseases in recent years. First findings have brought into the open that the exosomes secreted by local cells in the myocardium layer and stem cells have an essential role in the repair of cardiac damage because they involve pro-angiogenic, pro-survival, anti-fibrotic, or anti-apoptotic molecules.ConclusionThis review has comprehensively discussed the rich cargo content of somatic and stem cell-derived exosomes, their regulatory mechanisms in amelioration of the pathophysiology of coronary artery disease, molecular interactions of exosomal cargo contents, strengths, and limitations of exosomal strategies.
Keywords: Exosomes; Cardiac repair; Coronary artery disease; Myocardial infarction; ACUTE MYOCARDIAL-INFARCTION; INHIBIT CARDIOMYOCYTE APOPTOSIS; EXTRACELLULAR VESICLES; ENDOTHELIAL-CELLS; ISCHEMIA/REPERFUSION INJURY; PROMOTE ANGIOGENESIS; TRANSFERRIN RECEPTOR; THERAPEUTIC TARGET; NONCODING RNAS; HEART-FAILURE; Cardiovascular System & Cardiology